Blastomeres aggregation as an efficient alternative for trophoblast culture from porcine parthenogenetic embryos. (19th May 2015) - Saadeldin, Islam M.; Kim, Su Jin; Lee, Byeong Chun
<x xml:space="preserve">Abstract</x> Zona pellucida free (ZPF) oocytes were cultured after electrical activation to allow blastomeres aggregation and compared to ZP intact (ZPI) oocytes. In feeder‐dependent conditions, the trophoblast attachment and primary outgrowths were significantly higher in ZPF than in ZPI groups. In feeder‐free conditions, trophoblast attachment and typical morphological trophoblast primary outgrowths were observed in ZPF group. The primary colonies derived from the ZPF embryos in both culture conditions were able to establish secondary and tertiary colonies and showed mRNA expression of CDX2, TEAD4 and KRT8 as trophoblast markers, while outgrowths from the ZPI embryos could not grow beyond primary colonies.